2016
DOI: 10.1175/jpo-d-15-0216.1
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Kerguelen Plateau on the Ocean Circulation

Abstract: The Kerguelen Plateau is a major topographic feature in the Southern Ocean. Located in the Indian sector and spanning nearly 2000 km in the meridional direction from the polar to the subantarctic region, it deflects the eastward-flowing Antarctic Circumpolar Current and influences the physical circulation and biogeochemistry of the Southern Ocean. The Kerguelen Plateau is known to govern the local dynamics, but its impact on the large-scale ocean circulation has not been explored. By comparing global ocean num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 60 publications
0
15
0
Order By: Relevance
“…This could also be relevant to some other regions of the Southern Ocean where the ACC interacts with subpolar gyres as described in Wang et al. (2016).…”
Section: Resultsmentioning
confidence: 73%
See 2 more Smart Citations
“…This could also be relevant to some other regions of the Southern Ocean where the ACC interacts with subpolar gyres as described in Wang et al. (2016).…”
Section: Resultsmentioning
confidence: 73%
“…In the absence of small-scale topography, the ACC fronts also tend to shift equatorward. Similar meridional shift of the fronts is investigated in Wang et al (2016), where they show that, in response to the removal of Kerguelen Plateau (KP), the Indian Ocean part of the ACC shifts poleward, which leads to a warm anomaly in the upper North Atlantic and the corresponding decrease of the North Atlantic Deep Water (NADW) formation. In addition, their results indicate that the southward shift of the ACC in the no-KP simulation makes the Weddell Gyre warmer and saltier, which reduces the formation of Antarctic Bottom Water (AABW), thereby influencing the global thermohaline circulation.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…The mean zonal momentum balance should be between atmospheric wind forcing and bottom form stress across submarine ridges, seamounts, and land masses (Munk and Palmén, 1951), although boundary conditions play a role because the present model domain does not cover the whole Pacific Ocean. Following the methodology described in Masich et al (2015) and Wang et al (2016), zonal TFS is computed as the pressure difference between the eastern and western face of a topographic feature divided by the width of the feature; thus, it is assumed to be uniformly distributed within the feature. The TFS represents the momentum transfer from the ocean into the land masses, acting to dissipate the ocean momentum, which is primarily fed by atmospheric winds.…”
Section: Modifications To the Topographic Form Stressmentioning
confidence: 99%
“…Karnauskas et al (2007) used these kinds of bathymetry perturbation experiments to understand the effect of the Galápagos islands on the equatorial Pacific cold tongue using a reduced-gravity OGCM. Another study using a similar methodology was reported by Wang et al (2016), where Massachusetts Institute of Technology general circulation model (MITgcm; Marshall et al, 1997) simulations were used to study the effect of the Kerguelen Plateau on Southern Ocean circulation. Note that the Galápagos islands and the Kerguelen Plateau are relatively large topographic features when com-pared to Palau.…”
Section: Introductionmentioning
confidence: 99%